Rheumatoid arthritis, women's health, and pregnancy | مرض التهاب المفاصل الروماتويدي وصحة المرأة والحمل - Al Anzi | العنزي, Fahida bint Muhammad | فهيده بنت محمد (2024)
Rheumatoid arthritis is considered the most common rheumatic disease in the world. It is a chronic disease that causes pain and swelling in the joints, and may affect other organs such as the lungs, skin, eyes, and heart. Rheumatoid arthritis does not affect a woman's fertility and ability to get pregnant in general, but many changes occur in the immune system during pregnancy, as a result of changes in female hormone levels when planning pregnancy. | يُعتبر مرض التهاب المفاصل الروماتويدي أكثر الأمراض الروماتيزمية انتشارًا في العالم، وهو مرض مزمن يسبب آلامًا وتورمات في المفاصل، وقد يؤثر على الأعضاء الأخرى كالرئتين والجلد والعيون والقلب. مرض التهاب المفاصل الروماتويدي لا يؤثر على خصوبة المرأة وقدرتها على الحمل بشكل عام، ولكن تحدث العديد من التغييرات في جهاز المناعة أثناء الحمل، وذلك نتيجة استجابة للتغيّرات في مستويات الهرمونات الأنثوية عند التخطيط للحمل